Existence and uniqueness of solution for Cahn-Hilliard hyperbolic phase field system with Dirichlet boundary conditions and polynomial potential - Bissouesse, A. J.; Moukoko, Daniel; Langa, Franck; Batchi, Macaire (International Journal of Applied Mathematical Research, 2018)
Our aim in this article is to study the existence and the uniqueness of solution for Cahn-Hilliard hyperbolic phase-field system, with initial conditions, homogeneous Dirichlet boundary conditions, polynomial potential in a bounded and smooth domain.
Keywords: Cahn-Hilliard hyperbolic phase-field system; polynomial potential; Dirichlet boundary conditions.